2022
DOI: 10.47391/jpma.1410
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, causative organisms and sensitivity patterns of infective keratitis in a tertiary care hospital in Rawalpindi

Abstract: Objective: To determine the risk factors, causative organisms, sensitivity patterns and treatment outcomes of infective corneal ulcers. Methods: The is a prospective cohort study carried out from January 2018 to December 2019 at the Department of Ophthalmology, Fauji Foundation Hospital (FFH) Rawalpindi. A total of 65 eyes of 65 patients of corneal ulcer meeting the inclusion criteria were evaluated and corneal scrapes were sent for microbiological assessment.  Variables studied were age, gender, risk factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Female preponderance in this study was primarily due to the use of contact lenses among females [ 17 ]. However, another study done in Pakistan showed that (61.5%) of patients were female and 38.4% of patients were male among the 65 cases of infective keratitis included in the study [ 18 ]. Hence, the gender distribution among the cases of corneal ulceration may vary depending on the country in which the study is being conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Female preponderance in this study was primarily due to the use of contact lenses among females [ 17 ]. However, another study done in Pakistan showed that (61.5%) of patients were female and 38.4% of patients were male among the 65 cases of infective keratitis included in the study [ 18 ]. Hence, the gender distribution among the cases of corneal ulceration may vary depending on the country in which the study is being conducted.…”
Section: Discussionmentioning
confidence: 99%